Enhancing Innovative Behavior of Indonesian Secondary School Teachers Through Happiness at Work: An Implementation of ICT-Based Training - Anggun Resdasari Prasetyo; Anissa Lestari Kadiyono; Marina Sulastiana; Zainal Abidin (Human Behavior and Emerging Technologies)
The Indonesian government has implemented an ICT-based training to improve the innovative behavior of junior high school teachers. This study evaluates whether psychological aspects such as happiness at work play a role in shaping these behaviors. This study aims to examine the theoretical model of happiness at work as a mediator for the influence of proactive personality and perception of the school climate on teachers’ innovative behavior in digitalization and also compares whether ICT-based training implemented by the government increases happiness at work models on ICT and non-ICT teachers. This study uses the concurrent embedded design mixed methods; quantitative methods are used as the main focus of the study, while qualitative methods are used to strengthen quantitative data. The quantitative method uses four measuring instruments to prove the research model using SEM and a comparative analysis of ICT-based training implementation using multigroup SEM. The qualitative method is an exploratory approach with content analysis of open-ended questions to explore teachers in digitalization. The sample was 960 ICT teachers and 958 non-ICT teachers. The results of this research model proved that happiness at work is a mediator for proactive personality and perceived school climate in teachers’ innovative behavior in digitalization. In addition, the ICT-based training has been proven to strengthen the happiness at work model on ICT teachers. The results of this study have implications, namely, that schools are expected to be able to optimize happiness in the workplace and teacher recruitment selection involves proactive personality assessment.